Association among cardiorespiratory fitness, plasma biomarkers of pathology and astrocyte reactivity, and cognition in autosomal-dominant Alzheimer's disease. - Guzmán-Vélez, Edmarie; Aguillón, David; Rivera-Hernández, Angelys; Baena, Ana Y; Londoño-Sotomayor, Natalia; Picard, Glen; Kramer, Arthur F; Arnold, Steven E; Caraballo-Gracia, Domingo I; Taylor, J Andrew; Quiroz, Yakeel T (J Alzheimers Dis, 2025)
BackgroundHigh cardiorespiratory fitness has been associated with greater neuroplasticity, and slower neurodegeneration and cognitive decline in healthy adults. Yet, less is known about whether low-to-intermediate cardiorespiratory fitness is associated with lower markers of disease progression in the preclinical stage of Alzheimer's disease (AD).ObjectiveWe investigated whether cardiorespiratory fitness was associated with plasma biomarkers for AD-related pathology, neural injury and astrocyte reactivity, and episodic memory in Presenilin-1 E280A carriers without dementia from the world's largest kindred with autosomal-dominant AD.MethodsTwenty-seven mutation carriers (25 cognitively unimpaired, 2 with mild cognitive impairment; ages: μ=30.22 years, SD = 5.24; 74% female) participated in the study. Participants underwent a graded aerobic fitness test to assess cardiorespiratory fitness, measured in maximum metabolic equivalent of task (MET). Plasma biomarkers included amyloid 42/40, phosphorylated tau-181, neurofilament light chain, and glial fibrillary acidic protein. Participants completed the Consortium to Establish a Registry for AD word list learning and delayed recall. We conducted multiple linear regressions controlling for age, sex, and years of education.ResultsFourteen participants' MET values were indicative of low cardiorespiratory fitness (< MET), and 13 participants' MET values of intermediate cardiorespiratory fitness (9-14 MET). METs were not associated with age, biomarkers, or episodic memory.ConclusionsOur findings suggest that low-to-intermediate cardiorespiratory fitness may not be associated with biomarkers for AD-related pathology, neural injury and astrocyte reactivity, or memory in people at genetic risk for dementia. Longitudinal studies and randomized-controlled trials are needed to better understand the relationships among cardiorespiratory fitness and AD progression.

Effect of Metformin on Plasma and Cerebrospinal Fluid Biomarkers in Non-Diabetic Older Adults with Mild Cognitive Impairment Related to Alzheimer's Disease. - Weinberg, Marc S; He, Yingnan; Kivisäkk, Pia; Arnold, Steven E; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a complicated condition involving multiple metabolic and immunologic pathophysiological processes that can occur with the hallmark pathologies of amyloid-β, tau, and neurodegeneration. Metformin, an anti-diabetes drug, targets several of these disease processes in in vitro and animal studies. However, the effects of metformin on human cerebrospinal fluid (CSF) and plasma proteins as potential biomarkers of treatment remain unexplored. OBJECTIVE: Using proteomics data from a metformin clinical trial, identify the impact of metformin on plasma and CSF proteins. METHODS: We analyzed plasma and CSF proteomics data collected previously (ClinicalTrials.gov identifier: NCT01965756, conducted between 2013 and 2015), and conduced bioinformatics analyses to compare the plasma and CSF protein levels after 8 weeks of metformin or placebo use to their baseline levels in 20 non-diabetic patients with mild cognitive impairment (MCI) and positive AD biomarkers participants. RESULTS: 50 proteins were significantly (unadjusted p < 0.05) altered in plasma and 26 in CSF after 8 weeks of metformin use, with 7 proteins in common (AZU1, CASP-3, CCL11, CCL20, IL32, PRTN3, and REG1A). The correlation between changes in plasma and CSF levels of these 7 proteins after metformin use relative to baseline levels was high (r = 0.98). The proteins also demonstrated temporal stability. CONCLUSIONS: Our pilot study is the first to investigate the effect of metformin on plasma and CSF proteins in non-diabetic patients with MCI and positive AD biomarkers and identifies several candidate plasma biomarkers for future clinical trials after confirmatory studies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Double-Blind Method; Female; Humans; Hypoglycemic Agents; Male; Metformin; Middle Aged; Proteomics

Association of Cancer History with Alzheimer's Disease Dementia and Neuropathology. - Yarchoan, Mark; James, Bryan D; Shah, Raj C; Arvanitakis, Zoe; Wilson, Robert S; Schneider, Julie; Bennett, David A; Arnold, Steven E (J Alzheimers Dis, 2017)
BACKGROUND: Cancer and Alzheimer's disease (AD) are common diseases of aging and share many risk factors. Surprisingly, however, epidemiologic data from several recent independent cohort studies suggest that there may be an inverse association between these diseases. OBJECTIVE: To determine the relationship between history of cancer and odds of dementia proximate to death and neuropathological indices of AD. METHODS: Using data from two separate clinical-pathologic cohort studies of aging and AD, the Religious Orders Study (ROS) and the Rush Memory and Aging Project (MAP), we compared odds of AD dementia proximate to death among participants with and without a history of cancer. We then examined the relation of history of cancer with measures of AD pathology at autopsy, i.e., paired helical filament tau (PHFtau) neurofibrillary tangles and amyloid-β load. RESULTS: Participants reporting a history of cancer had significantly lower odds of AD (OR 0.70 [0.55-0.89], p = 0.0040) proximate to death as compared to participants reporting no prior history of cancer. The results remained significant after adjusting for multiple risk factors including age, sex, race, education, and presence of an APOEɛ4 allele. At autopsy, participants with a history of cancer had significantly fewer PHFtau tangles (p < 0.001) than participants without a history of cancer, but similar levels of amyloid-β. CONCLUSIONS: Cancer survivors have reduced odds of developing AD and a lower burden of neurofibrillary tangle deposition.

Odor Identification Screening Improves Diagnostic Classification in Incipient Alzheimer's Disease. - Quarmley, Megan; Moberg, Paul J; Mechanic-Hamilton, Dawn; Kabadi, Sushila; Arnold, Steven E; Wolk, David A; Roalf, David R (J Alzheimers Dis, 2017)
BACKGROUND: Measurements of olfaction may serve as useful biomarkers of incipient dementia. Here we examine the improvement in diagnostic accuracy of Alzheimer's disease (AD) and mild cognitive impairment (MCI) when assessing both cognitive functioning and odor identification. OBJECTIVE: To determine the utility of odor identification as a supplementary screening test in incipient AD. METHODS: Sniffin' Sticks Odor Identification Test (SS-OIT) and the Montreal Cognitive Assessment (MoCA) were administered in 262 AD, 174 MCI [150 amnestic (aMCI), and 24 non-amnestic (naMCI)], and 292 healthy older adults (HOA). RESULTS: Odor identification scores were higher in HOA relative to MCI or AD groups, and MCI outperformed AD. Odor identification scores were higher in aMCI single domain than aMCI multiple domain. Complementing MoCA scores with the SS-OIT significantly improved diagnostic accuracy of individuals with AD and MCI, including within MCI subgroups. DISCUSSION: Odor identification is a useful supplementary screening tool that provides additional information relevant for clinical categorization of AD and MCI, including those who are at highest risk to convert to AD.

Within-Individual Variability: An Index for Subtle Change in Neurocognition in Mild Cognitive Impairment. - Roalf, David R; Quarmley, Megan; Mechanic-Hamilton, Dawn; Wolk, David A; Arnold, Steven E; Moberg, Paul J (J Alzheimers Dis, 2016)
BACKGROUND: The transition from mild cognitive impairment (MCI) to Alzheimer's disease is characterized by a decline in cognitive performance in many domains. Cognitive performance profiles in MCI are heterogeneous, however, and additional insights into markers of incipient dementia are needed. Typically, studies focus on average or mean performance, but ignore consistency of performance across domains. WIV (within-individual variability) provides an index of this consistency and is a potential marker of cognitive decline. OBJECTIVE: To use neurocognitive data from the Alzheimer's Disease Neuroimaging Initiative cohort to measure neurocognitive variability. METHODS: The utility of WIV was measured, in addition to global neurocognitive performance (GNP), for identifying AD and MCI. In addition, the association between changes in neurocognitive variability and diagnostic transition over 12 months was measured. RESULTS: As expected, variability was higher in AD and MCI as compared to healthy controls; GNP was lower in both groups as compared to healthy subjects. Global neurocognitive performance alone best distinguished those with dementia from healthy older adults. Yet, for individuals with MCI, including variability along with GNP improved diagnostic classification. Variability was higher at baseline in individuals transitioning from MCI to AD over a 12-month period. CONCLUSION: We conclude that variability offers complementary information about neurocognitive performance in dementia, particularly in individuals with MCI, and may provide beneficial information about disease transition.

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction